DEVELOPMENT of MICROSATELLITE MARKERS FOR PIMENTA PSEUDOCARYOPHYLLUS (MYRTACEAE), A WILD SOUTH AMERICAN SPECIES - Morgante, Patrícia Gleydes [UNESP]; Sebastiao, Isis [UNESP]; Duarte Silveira, Lilian Elena [UNESP]; Mori, Gustavo M.; Conte, Monica; Coffani-Nunes, Joao Vicente [UNESP] (Botanical Soc Amer Inc, 2012)
Premise of the study: We developed the first set of microsatellite markers for Pimenta pseudocaryophyllus to support further studies on genetic diversity and to inform conservation strategies.Methods and Results: The microsatellite-enriched library approach was used to isolate and characterize 12 new molecular markers. It was possible to detect 11 polymorphic microsatellite loci and one monomorphic locus. The polymorphism information content ranged from 0.317 to 0.869.Conclusions: These molecular markers will be valuable tools to aid in understanding the biology of P. pseudocaryophyllus and to detect ongoing consequences of its exploitation, in the context of conservation genetics.
Keywords: genetic diversity; microsatellite-enriched library; molecular markers; Myrtaceae; Pimenta pseudocaryophyllus; population genetics